A multicenter trial on the predictors of different subtypes of hemorrhagic infarction after thrombolysis - Mohamed G. Zeinhom; Sherihan Rezk Ahmed; Ahmed Mohamed Kohail; Islam Fathallah Mohamed Kamel; ALshimaa Mahfouz Abdelrahman; Omar M. AL-Nozha; Mohamed Almoataz; Tarek Youssif Omar Youssif; Ahmed Mohamed Ali Daabis; Hossam Mohamed Refat; Ahmed Ahmed Mohamed Kamal Ebied; Ahmed Elbassiouny; et al. (Scientific Reports)
Abstract Worldwide, stroke is a leading cause of long-term disability in adults. Alteplase is the only approved treatment for acute ischemic stroke (AIS) and results in an improvement in a third of treated patients. Most studies evaluated the post-alteplase haemorrhagic transformation of brain infarction as a homogeneous entity but we evaluated the predictors of each subtype of haemorrhagic transformation of brain infarction. Our trial included 616 AIS alteplase-treated patients. We evaluated the ability of different risk factors, clinical presentation, and imaging features to predict different haemorrhagic transformation (HT) subtypes. HT was seen in 152 patients (24.7%), higher NIHSS, cardioembolic stroke and atrial fibrillation were independent predictors of all ECASS-based subtypes of hemorrhagic infarction, in addition, anterior-circulation stroke was an independent predictor of hemorrhagic infarction type 1 (odds ratio [OR], 11.04; 95% CI, 9.81 to 12.70; P-value > 0.001) and type2 (OR, 11.89; 95% CI, 9.79 to 14.44; P-value > 0.001), while older age was also an independent predictor of parenchymal hematoma type1 (OR, 1.312; 95% CI, 1.245 to 1.912; P-value 0.02). In AIS patients treated with alteplase in Egypt and Saudi Arabia, higher NIHSS, cardioembolic stroke and atrial fibrillation were independent predictors of all ECASS-based subtypes of hemorrhagic infarction; in addition, anterior-circulation stroke was an independent predictor of hemorrhagic infarction type 1 and 2, while older age was also an independent predictor of parenchymal hematoma type1. Trial registration: (clinicaltrials.gov NCT06337175), retrospectively registered on 29/03/2024.